Packaging Waste Recycling: A Pathway to Climate Change Mitigation in Türkiye - Çapar, Berna; Kranert, Martin; Topkaya, Bülent (Fırat University, 2025)
Climate change has significantly affected numerous aspects of our planet, with weather patterns being one of the most visibly impacted. The growing concentration of greenhouse gases (GHGs) in the atmosphere traps more heat, leading to disruptions in weather systems and amplifying the challenges posed by climate change. The main sources of greenhouse gas (GHG) emissions are fossil fuels, with the largest contributors being the power generation, transportation, and industrial combustion sectors. Additional significant sources include agriculture, fuel extraction, buildings, and waste management both globally and in Türkiye. Recycling packaging waste plays a vital role in mitigating climate change by reducing GHG emissions and conserving energy. It minimizes waste sent to landfills and promotes a circular economy, enabling the continual reuse and recycling of materials. This process decreases the reliance on new raw materials, further reducing environmental impacts and contributing to a more sustainable future.

İklim değişikliği, gezegenimizin birçok yönünü önemli ölçüde etkilemiş olup, hava olayları en görünür şekilde etkilenen alanlardan biridir. Atmosferde artan sera gazı (GHG) yoğunluğu, daha fazla ısının tutulmasına neden olarak hava sistemlerinde bozulmalara yol açmakta ve iklim değişikliğinin yarattığı zorlukları artırmaktadır. Sera gazı (GHG) emisyonlarının başlıca kaynakları fosil yakıtlar olup, en büyük katkıyı enerji üretimi, ulaşım ve endüstriyel yanma sektörleri sağlamaktadır. Ayrıca, tarım, yakıt çıkarma, binalar ve atık yönetimi hem dünya genelinde hem de Türkiye’de önemli diğer önemli kaynaklar arasında yer almaktadır. Ambalaj atıklarının geri dönüşümü, sera gazı emisyonlarını azaltarak ve enerji tasarrufu sağlayarak iklim değişikliğiyle mücadelede hayati bir rol oynamaktadır. Bu süreç, depolama alanlarına gönderilen atık miktarını azaltmakta ve malzemelerin sürekli olarak yeniden kullanılıp geri dönüştürülmesini sağlayan döngüsel bir ekonomiyi teşvik etmektedir. Böylece yeni ham maddelere olan bağımlılık azalmakta, çevresel etkiler en aza indirilmekte ve daha sürdürülebilir bir geleceğe katkı sağlanmaktadır.
Ambalaj Atığı Geri Dönüşüm: Türkiye’de İklim Değişikliğiyle Mücadele için Bir Yol
Keywords: Waste Management; Reduction; Reuse and Recycling; Atık Yönetimi; Azaltma; Yeniden Kullanım ve Geri Dönüşüm